Assessing the effects of restoration and conservation on gaseous carbon fluxes and climate mitigation potential across six European coastal wetlands - Miguel Cabrera-Brufau; Camille Minaudo; Katrin Attermeyer; Alba Camacho-Santamans; Rafael Carballeira; Benjamin Misteli; Jorge Montes-Pérez; Daniel Morant; Biel Obrador; Antonio Picazo; Carlos Rochera; Mihai Adamescu; et al. (Ecological Engineering, 2026)

Invasive macrophytes as refuge and habitat for zooplankton: insights from a mesocosm experiment - Benjamin Misteli; Christophe Piscart; Stéphanie Llopis; Aijuan Liao; Gabrielle Thiébaut; Alexandrine Pannard (Hydrobiologia, 2026)

Nutrients on the move: Investigating large scale fatty acid exports from European ponds via emerging insects - Lena Fehlinger; Fernando Chaguaceda; Pietro Tirozzi; Marina Tomás‐Martín; Ellinor Jakobsson; Teofana Chonova; Benjamin Misteli; Alberto Scotti; Jorge F. Henriques; Juan Rubio‐Ríos; Daniel Morant; Pierre Marle; et al. (Limnology and Oceanography, 2025)
Permanent ponds are key landscape units that supply various ecosystem services. Notably, the export of aquatic subsidies to land via emerging insects may significantly influence terrestrial food webs. Polyunsaturated fatty acids (PUFA), which enhance consumer fitness, are among the essential exported components. The patterns and drivers of dietary exports from ponds via insects remain poorly known, particularly at continental scales. We analyzed the exports of biomass, lipid, and fatty acid contents from emerging insects, sampled in 36 ponds across 11 European countries, from 36°N to 59°N and from 26°W to 19°E, over four seasons. We found that biomass and fatty acid exports decreased with increasing latitude and were higher in spring and summer. Seasonal effects also increased with higher latitudes. Temperature was the most important predictor of insect biomass, explaining 27.6% of the total variation and showing an unimodal response. Thus, increasing temperature may promote exports in colder regions and seasons but may negatively influence biomass exports in already warm regions. The exports of total lipids, PUFA, and eicosapentaenoic acid were correlated to exported biomass, while those of docosahexaenoic acid were linked to the emergence of Chaoboridae. Our findings indicated that PUFA contents were affected by taxonomic insect community composition and pond trophic state (indicated by chlorophyll a ). Two of the correlates identified here (temperature and trophic state) are influenced by anthropogenic activity via climate and land use change, respectively. Thus, human activity impacts the food webs in and around ponds by influencing the quantity and quality of nutritional exports.

Does Perceived Nuisance Abundance of Water Plants Match with Willingness-to-Pay for Removal? Contrasts Among Different User Categories - Jan E. Vermaat; Kirstine Thiemer; Bart Immerzeel; Susanne C. Schneider; Keneilwe Sebola; Julie Coetzee; Antonella Petruzzella; Samuel N. Motitsoe; Mathieu Baldo; Benjamin Misteli; Gabrielle Thiébaut; Sabine Hilt; et al. (Environmental Management, 2025)
Dense beds of water plants can be perceived as nuisance, but this perception, however, may not be similar for different user categories, and this may affect their willingness-to-pay (WTP) for plant removal. A questionnaire survey was used to test this for residents and visitors and find underlying socio-cultural or economic drivers. We studied five cases where nuisance water plant growth is managed: the rivers Otra (Norway) and Spree (Germany), and the lakes Kemnade (Germany), Grand-Lieu (France), and Hartbeespoort Dam (South Africa). We used a different payment vehicle for residents (annual household tax) and visitors (tourist tax). The survey included questions on days spent on specific types of activity per year, the importance attached to different functions and activities, overall environmental attitude, perception of the plants, socio-demographic respondent characteristics and WTP for increased plant removal. We observed no increase in WTP for increased removal in most sites. The two most important drivers of variation in current WTP were income, and whether respondents were engaged in boating and angling and thus perceived the plants negatively. Variation in WTP among sites was considerable, and mainly related to the mixture of activities among respondents. Differences between residents and visitors were less important than those among sites. Our observations bear importance for water management: information on differences in experienced nuisance among user categories and the frequency of use by these categories is useful as guidance for the design and implementation of any plant removal plan.

Causes of macrophyte mass development and management recommendations - Susanne C. Schneider; Julie A. Coetzee; Elena Fukasawa Galvanese; Sarah Faye Harpenslager; Sabine Hilt; Bart Immerzeel; Jan Köhler; Benjamin Misteli; Samuel N. Motitsoe; Andre A. Padial; Antonella Petruzzella; Anne Schechner; et al. (Science of The Total Environment, 2024)

Short-term effects of macrophyte removal on aquatic biodiversity in rivers and lakes - Benjamin Misteli; Alexandrine Pannard; Eirin Aasland; Sarah Faye Harpenslager; Samuel Motitsoe; Kirstine Thiemer; Stéphanie Llopis; Julie Coetzee; Sabine Hilt; Jan Köhler; Susanne C. Schneider; Christophe Piscart; et al. (Journal of Environmental Management, 2023)

Long-lasting effects of experimental flow intermittency on alpine stream macroinvertebrates (Val Roseg, Switzerland) - Annemieke M. Drost; Andre R. Siebers; Amael Paillex; Benjamin Misteli; Edwin T. H. M. Peeters; Christopher T. Robinson (Hydrobiologia, 2022)
Changing weather patterns and receding glaciers are predicted to increase flow intermittency in alpine streams. If aquatic macroinvertebrate communities largely comprise taxa adapted to perennial flows, an increase in flow intermittency substantially reduces biodiversity and affects functional processes. We conducted a before-after-control-impact field experiment to examine how macroinvertebrate communities in an alpine headwater stream responded to and recovered from a repeated experimental increase in flow intermittency. Flow in one channel was manipulated to simulate increased summer intermittency (June–September) over two consecutive years, whilst an adjacent channel served as a control. We monitored the density of benthic macroinvertebrates, periphyton and organic matter at approximately monthly intervals over three years during the snow-free period. Before manipulation, both channels had similar ecological properties. The flow manipulation reduced the overall macroinvertebrate density, and especially the proportional rheophile density, across both years. Recovery of the macroinvertebrate community following experimental flow intermittency took more than a year, and longer than our study period. This could be due to long aquatic life stages, dispersal limitation and biotic interactions. We conclude that climate-induced changes in alpine stream flow regimes can lead to a fundamental shift in macroinvertebrate assemblages through local extinctions, mostly of rheophilic species.

Effects of an experimental increase in flow intermittency on an alpine stream - Andre R. Siebers; Amael Paillex; Benjamin Misteli; Christopher T. Robinson (Hydrobiologia, 2020)